no, after multiplying by 16 you get
10x + x = 11 + 16x
etc
5/8 x+1/16 x=11/16+x
16*(5/8 x+1/16 x) = 16(11/16+x)
80 + x + 16 + x= 11 + 16x
80 + 2x + 16 = 11 + 16x
-x = 18x (divide by 1)
x = 18
Did I do this correctly?
3 answers
10x + x = 11 + 16x, so the next step is:
11x = 11 + 16x (get x-terms on the left.)
-x = 11 (divide by -1.)
x = 11
Is this now correct?
11x = 11 + 16x (get x-terms on the left.)
-x = 11 (divide by -1.)
x = 11
Is this now correct?
11x = 11 + 16x
Subtracting 16x from both sides:
-5x = 11
Now divide by -5.
Subtracting 16x from both sides:
-5x = 11
Now divide by -5.